Integrating host plant resistance and molecular breeding to combat shoot fly in sorghum: A review - Sunilkumar, D; Parthasarathi, G; Vinoth, P; Kavithamani, D; Srinivasan, T; Subramaniam, G; Thamaraikannan, S; Indhu, S M; Karthikeyan, A; Senthil, N (Plant Science Today, 2025)
Sorghum is one of the major millet crops globally and is severely affected by various pests and diseases, with the shoot fly (Atherigona soccata) being one of the most damaging pests to sorghum production worldwide. This pest primarily targets sorghum seedlings, causing yield losses of up to 90 %. Despite adopting various management practices, host plant resistance remains the most effective, economical and environment friendly method for controlling this pest. Conventional breeding strategies, which rely exclusively on phenotypic selection, have encountered significant challenges in developing cultivars with broad-spectrum resistance. In recent decades, significant efforts have been made to address these limitations by leveraging advancements in molecular breeding approaches, including Quantitative Trait Loci (QTL) mapping and Marker-Assisted Selection (MAS). These approaches have led to the identification of several resistant genotypes, QTLs and genes associated with shoot fly resistance in sorghum. However, progress in improving sorghum resistance to the shoot fly through molecular breeding remains limited. This review discusses the biology and impact of the shoot fly on sorghum, evaluates progress and constraints in molecular breeding for resistance, identifies existing research gaps and proposes future directions to enhance efforts in combating shoot fly resistance in sorghum.